A cost-effectiveness analysis of first-line toripalimab plus chemotherapy in advanced nonsquamous non-small cell lung cancer in China. Issue 3 (4th March 2023) - Zheng, Zhiwei; Zhu, Gaofeng; Cao, Xueqiong; Cai, Hongfu; Zhu, Huide
ABSTRACT: Background: This study compares first-line toripalimab with chemotherapy for advanced nonsquamous non-small cell lung cancer (NSCLC) from the perspective of the Chinese healthcare system. Research design and methods: A three-state Markov model was established to compare the quality-adjusted life years (QALYs) and incremental cost-effectiveness ratio (ICER) of first-line toripalimab plus chemotherapy versus chemotherapy. Clinical outcomes data were acquired from the CHOICE-01 clinical trials. Costs and utilities were gathered from regional databases or published publications. One-way sensitivity and probability sensitivity analyses were used to investigate the stability of the model parameters. Results: First-line toripalimab treatment for advanced nonsquamous NSCLC resulted in an incremental cost of $16, 214.03 and added 0.77 QALYs compared to chemotherapy, which had an ICER of $21, 057.18 per QALY gained. The ICER was substantially lower than the willingness to pay (WTP) threshold in China, which was $37, 663.26 per QALY. The toripalimab cycle used was shown to have the greatest impact on the ICERs, according to sensitivity analysis, although none of the factors significantly affected the model's outcomes Conclusions: Toripalimab plus chemotherapy is likely to be a cost-effective option compared with chemotherapy alone for patients with advanced nonsquamous NSCLC from the perspective of the Chinese healthcare system.